SURF – SUrvey of Risk Factor management: first report of an international audit. (July 2014) - Cooney, MT; Reiner, Z; Sheu, W; Ryden, L; Sutter, J de; De Bacquer, D; DeBacker, G; Mithal, A; Chung, N; Lim, YT; Dudina, A; Reynolds, A; et al.
Background: Despite the fact that subjects with established coronary heart disease (CHD) are at high risk of further events and deserve meticulous secondary prevention, current audits such as EUROASPIRE show poor control of major risk factors. Ongoing monitoring is required. We present a new risk factor audit system, SURF (Survey of Risk Factor management), that can be conducted much more quickly and easily than existing audit systems and has the potential to allow hospitals of all sizes to participate in a unified international audit system that will complement EUROASPIRE. Initial experience indicates that SURF is truly simple to undertake in an international setting, and this is illustrated with the results of a substantive pilot project conducted in Europe and Asia. Methods: The data collection system was designed to allow rapid and easy data collection as part of routine clinic work. Consecutive patients (aged 18 and over) with established CHD attending outpatient cardiology clinics were included. Information on demographics, previous coronary medical history, smoking history, history of hypertension, dyslipidaemia or diabetes, physical activity, attendance at cardiac rehabilitation, cardiac medications, lipid and glucose levels (and HbA1c in diabetics) if available within the last year, blood pressure, heart rate, body mass index, and waist circumference were collected using a one-page data collection sheet. Years spent in full time education was added as an additional question during the pilot phase. Results: Three European countries − Ireland ( n  = 251), Belgium ( n  = 122), and Croatia ( n  = 124) − and four Asian countries − Singapore ( n  = 142), Taiwan ( n  = 334), India ( n  = 97), and Korea ( n  = 45) − were included in the pilot study. The results of initial field testing were confirmed in that it proved possible to collect data within 60−90 seconds per subject. There was poor control of several risk factors including high levels of physical inactivity (41−45%), overweight and obesity (59−78%), and ongoing smoking (15%). There were lower levels of individuals attending cardiac rehabilitation in Asia. More Europeans than Asians reached the low-density lipoprotein cholesterol target of <2.5mmol/l (66 vs. 59%) reflecting differences in medication usage. However, blood pressure control was superior in Asia, with 71% <140/90 compared with 66% of Europeans (NS). Conclusions: This phase of SURF has confirmed its ease of use which should allow wide participation and the collection of representative risk factor data in subjects with CHD as well as ongoing data collection to monitor secular trends in risk factor control. Notwithstanding that this is a pilot study, the results suggest that risk factor control, particularly for lifestyle-related measures, is poor in both Europe and Asia.